Rooftop view of downtown San Jose from East to South east - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Rooftop view of downtown San Jose from East to South. From the middle of the image to the far left, Santa Clara street can be seen heading East, past the Mercury Herald, the First National Bank, the Bank of San Jose, and the Bank of Italy. From the middle of the image to the far right, Market Street can be seen heading Southeast, past St. Joseph's Cathedral and into San Jose City Hall and the Market Street Plaza.